Perspektif Islam dalam meningkatkan spiritualitas melalui kajian matematika - Alyyah, Afifatul (Maliki Interdisciplinary Journal, 2024)
Islam is one of the religions in Indonesia and has the most followers throughout the world. Islam is a religion that is rahmatallil 'alamin which upholds the value of balance in life between one creature and another, which teaches about spirituality to get closer to Allah SWT. The Islamic religion places great emphasis on its followers learning what they do not know. One way is to understand mathematical concepts to increase faith and understanding through mathematical studies. From an Islamic perspective, mathematical concepts are able to increase the faith of Muslims. Apart from that, the Al-Qur'an also states that there are verses that explain mathematical concepts such as numbers, number relations, number operations, estimation, equations and inequalities, and so on. Understanding the verses of the Qur'an regarding mathematical explanations will be able to provide an approach to Allah SWT. So, mathematics for Muslims is very necessary to improve spirituality as a servant before Allah SWT.